Optimality in Multiobjective Subset Fractional Programming Involving Generalized Type \(n\)-Functions (Journal of Informatics and Mathematical Sciences, 2018)
In this paper we investigate the optimality in multiobjective subset fractional programming involving generalized type \(n\)-functions under \((F,α,ρ, d)\)-type-I function. The results presented in this paper extend several results from the literature.
Keywords: Sufficiency; Fractional programming; \(n\)-functions